2015
DOI: 10.1016/j.agwat.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of groundwater on cotton growth and root zone water balance using Hydrus-1D coupled with a crop growth model

Abstract: a b s t r a c tGroundwater is an important factor that needs to be considered when evaluating the water balance of the soil-plant-atmosphere system and the sustainable development of arid oases. However, the impact of shallow groundwater on the root zone water balance and cotton growth is not fully understood. In this study, we have first analyzed the influence of the groundwater table depth on the seasonal maximum leaf area index of cotton, the average seasonal water stress, cotton yield, actual transpiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Similarly, Deb et al (2011) reported RMSE values similar to our study at various depths for water distribution simulation under a pecan tree. However, Han et al (2015) recorded higher RMSE during calibration than validation for cotton.…”
Section: Comparison Of Measured and Simulated Water Contentsmentioning
confidence: 91%
“…Similarly, Deb et al (2011) reported RMSE values similar to our study at various depths for water distribution simulation under a pecan tree. However, Han et al (2015) recorded higher RMSE during calibration than validation for cotton.…”
Section: Comparison Of Measured and Simulated Water Contentsmentioning
confidence: 91%
“…Zhou et al (2012) coupled HYDRUS-1D with the WOFOST crop growth model (Boogaard et al, 1998), and used the resulting code to simulate the growth and yield of irrigated wheat and maize (Li et al, , 2014. Han et al (2015) similarly coupled HYDRUS-1D with a simplified crop growth version used in SWAT, based on the EPIC root growth model (Williams et al, 1989). They used the coupled model to simulate the contribution and impact of groundwater on cotton growth and root zone water balance.…”
Section: Root Growthmentioning
confidence: 99%
“…Similarly, HYDRUS have been coupled successfully with existing crop and root growth models (e.g., Groenendyk et. al., 2012;Han et al, 2015;Hartmann et al, 2017;Li et al, 2014;Peña-Haro et al, 2012;Wang et al, 2014;Zhou et al, 2012). For example, Peña-Haro et al (2012) integrated WOFOST, a crop growth and production model, with HYDRUS-1D as well as with MODFLOW-2000 (Harbaugh et al, 2000), the latter being a saturated flow model.…”
Section: Introductionmentioning
confidence: 99%